Jak Mikołaj Sęp Szarzyński czytał psalmy - analiza "V pieśni na kształt psalmu LXX" - Kuran, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The subject of this article is paraphrase of psalm LXX wrote by Mikołaj Sęp Szarzyński. Szarzyński's text was compared with the Vulgate and translation prepared by Jan Leopolita (1561). Because of this comparison we may observe how Szarzy!ski modified original text. The paraphrase indicates personal reading of the psalm. Thanks to own sensitivity and specific perception of world, the poet included this psalm in his most personal poetry. The translation of the psalm LXX impacted logically poet s works, especially this area which treats about human kindness, weakness and relations human-God.